Identifying hypertensive disorders of pregnancy, a comparison of two epidemiologic definitions - Cheetham, T. Craig; Shortreed, Susan M.; Avalos, Lyndsay A.; Reynolds, Kristi; Holt, Victoria L.; Easterling, Thomas R.; Portugal, Cecilia; Zhou, Hui; Neugebauer, Romain S.; Bider, Zoe; Idu, Abisola; Dublin, Sascha (Frontiers in Cardiovascular Medicine, 2022)
Introduction Studies of hypertension in pregnancy that use electronic health care data generally identify hypertension using hospital diagnosis codes alone. We sought to compare results from this approach to an approach that included diagnosis codes, antihypertensive medications and blood pressure (BP) values. Materials and methods We conducted a retrospective cohort study of 1,45,739 pregnancies from 2009 to 2014 within an integrated healthcare system. Hypertensive pregnancies were identified using the “BP-Inclusive Definition” if at least one of three criteria were met: (1) two elevated outpatient BPs, (2) antihypertensive medication fill plus an outpatient hypertension diagnosis, or (3) hospital discharge diagnosis for preeclampsia or eclampsia. The “Traditional Definition” considered only delivery hospitalization discharge diagnoses. Outcome event analyses compared rates of preterm delivery and small for gestational age (SGA) between the two definitions. Results The BP-Inclusive Definition identified 14,225 (9.8%) hypertensive pregnancies while the Traditional Definition identified 13,637 (9.4%); 10,809 women met both definitions. Preterm delivery occurred in 20.9% of BP-Inclusive Definition pregnancies, 21.8% of Traditional Definition pregnancies and 6.6% of non-hypertensive pregnancies; for SGA the numbers were 15.6, 16.3, and 8.6%, respectively (p < 0.001 for all events compared to non-hypertensive pregnancies). Analyses in women meeting only one hypertension definition (21–24% of positive cases) found much lower rates of both preterm delivery and SGA. Conclusion Prevalence of hypertension in pregnancy was similar between the two study definitions. However, a substantial number of women met only one of the study definitions. Women who met only one of the hypertension definitions had much lower rates of adverse neonatal events than women meeting both definitions.